Hydroxysafflor Yellow A mitigated myocardial ischemia/reperfusion injury by inhibiting the activation of the JAK2/STAT1 pathway - Zhou, Donglai (Int J Mol Med, 2019)
Hydroxysafflor Yellow A (HSYA) may reduce ischemia/reperfusion (I/R) injury. However, the underlying molecular mechanisms remain unclear. The present study explored the effect and the mechanisms of HSYA on myocardial injury in vivo and in vitro. Myocardial infarct size was assessed by Evans blue/2,3,5-triphenyltetrazoliumchloride staining. Levels of cardiac troponin I (cTnI), interleukin-6 (IL-6), lactate dehydrogenase (LDH), superoxide dismutase (SOD) and malondialdehyde (MDA) were measured using commercial kits. Alteration of mitochondrial membrane potential (MMP) and reactive oxygen species (ROS) generation was determined by fluorescent signals. Apoptosis was detected by terminal deoxynucleotidyl-transferase-mediated dUTP nick-end labeling staining, flow cytometry assay and caspase-3 activity. Expression levels of the apoptosis-associated proteins were detected by reverse transcription quantitative polymerase chain reaction and western blot analysis. In vivo, animals treated with HSYA presented less severe myocardial injury and decreased janus kinase 2 (JAK2)/signal transducer and activator of transcription 1 (STAT1) activity, improved antioxidant capacity and decreased apoptosis. In vitro, compared with the hypoxia (H)/reoxygenation (R) + HSYA group, AG490 and S1491 treatment decreased the releases of cTnI, IL-6 and LDH and enhanced the resistance to oxidative stress by maintaining MMP and decreasing ROS generation. In addition, AG490 and S1491 were also identified to alleviate the H/R-induced apoptosis by inhibiting caspase 3 activity and modulating the expression levels of cleaved caspase-3, tumor necrosis factor receptor superfamily member 6 (Fas), Fas ligand, B-cell lymphoma 2 (Bcl-2) and Bcl-2-associated X protein. These data suggested that inactivation of the JAK2/STAT1 pathway strengthened the HSYA-induced protective effect in H/R-induced myocardial injury. In conclusion, the treatment of HSYA was effective in decreasing IR-induced myocardial injury, and this may be largely dependent on the JAK2/STAT1 pathway. Therefore, the present study provided a potential strategy to prevent myocardial I/R injury.